2016
DOI: 10.1016/j.celrep.2016.11.072
|View full text |Cite
|
Sign up to set email alerts
|

Human Beta Cells Produce and Release Serotonin to Inhibit Glucagon Secretion from Alpha Cells

Abstract: SUMMARY In the pancreatic islet serotonin is an autocrine signal increasing beta cell mass during metabolic challenges such as those associated with pregnancy or high-fat diet. It is still unclear if serotonin is relevant for regular islet physiology and hormone secretion. Here we show that human beta cells produce and secrete serotonin when stimulated with increases in glucose concentration. Serotonin secretion from beta cells decreases cAMP levels in neighboring alpha cells via 5-HT1F receptors and inhibits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
138
3
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(166 citation statements)
references
References 70 publications
9
138
3
5
Order By: Relevance
“…These findings do not preclude paracrine mechanisms observed in other studies; in fact, the studies of Almaca et al . () and Li et al . () were conducted in human islets – a paracrine environment very architecturally different from that of mouse islets (Brissova et al .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…These findings do not preclude paracrine mechanisms observed in other studies; in fact, the studies of Almaca et al . () and Li et al . () were conducted in human islets – a paracrine environment very architecturally different from that of mouse islets (Brissova et al .…”
Section: Discussionmentioning
confidence: 88%
“…; Ravier & Rutter, ), serotonin (Almaca et al . ), somatostatin (Hauge‐Evans et al . ) and urocortin3 (van der Meulen et al .…”
Section: Introductionmentioning
confidence: 99%
“…), paracrine (Almaca et al. ), juxtacrine (Hutchens and Piston ), neuronal (Rosario et al. ), hormonal (Pipeleers et al.…”
Section: Discussionmentioning
confidence: 99%
“…GLP-1 infusions in nondiabetic men have demonstrated that the plasma glucose-lowering action of GLP-1 is due to both a reduction in glucagon and increase in insulin secretion (Hare et al 2010). The regulation of glucagon secretion from the pancreatic a-cells remains obscure even under healthy conditions, with evidence for intrinsic (Zhang et al 2007), paracrine (Almaca et al 2016), juxtacrine (Hutchens and Piston 2015), neuronal (Rosario et al 2016), hormonal (Pipeleers et al 1985), and hepatic (Kim et al 2017) modulation. Furthermore, our knowledge of the cellular regulation of glucagon secretion comes from studies of rodent pancreatic islets, with a limited number of studies examining human a-cells (Cabrera et al 2006;MacDonald et al 2007;Spigelman et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The latter may play a role for the autoimmune attack in type-1 diabetes, the pro-inflammatory milieu associated with type-2 diabetes 83 , and βcell development during embryogenesis 84 . Finally, human β-cells also secrete serotonin (5hydroxytryptamine), which inhibits glucagon secretion from α-cells 85 . The effects of Epac activation by cAMP and sulfonylureas on fusion pore behavior are therefore likely to have profound consequences for intra-islet signaling.…”
Section: Discussionmentioning
confidence: 99%